2017
DOI: 10.1021/acs.jpclett.7b02893
|View full text |Cite
|
Sign up to set email alerts
|

How Inter- and Intramolecular Processes Dictate Aggregation-Induced Emission in Crystals Undergoing Excited-State Proton Transfer

Abstract: Aggregation-induced emission (AIE) offers a route for the development of luminescent technologies with high quantum efficiencies. Excited-state intramolecular proton transfer (ESIPT) coupled to AIE can produce devices with emission across the visible spectrum. We use a combination of theoretical models to determine the factors that mediate fluorescence in molecular crystals undergoing ESIPT. Using two materials based on 2'-hydroxychalcone as exemplar cases, we analyze how inter- and intramolecular processes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 58 publications
2
98
0
Order By: Relevance
“…In fact, some authors have claimed that the term AIE should be reserved for cases involving intermolecular electronic interactions, whereas the cases involving steric confinement should be classified as solid‐state enhanced emission . In any case, the significant role of the environment can be illustrated with several examples in the solid state, where small changes of the electronic structure by substitution, or changes in the relative orientation of neighboring molecules such as in polymorphic crystals lead to distinctive emissive properties from aggregation quenching to AIE . A better understanding of the interplay between intermolecular and intramolecular forces, as well as electronic versus steric effects, is essential to understand AIE in depth.…”
Section: Effect Of Intermolecular Interactions and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some authors have claimed that the term AIE should be reserved for cases involving intermolecular electronic interactions, whereas the cases involving steric confinement should be classified as solid‐state enhanced emission . In any case, the significant role of the environment can be illustrated with several examples in the solid state, where small changes of the electronic structure by substitution, or changes in the relative orientation of neighboring molecules such as in polymorphic crystals lead to distinctive emissive properties from aggregation quenching to AIE . A better understanding of the interplay between intermolecular and intramolecular forces, as well as electronic versus steric effects, is essential to understand AIE in depth.…”
Section: Effect Of Intermolecular Interactions and The Environmentmentioning
confidence: 99%
“…Another ESIPT AIEgen where aCIl ies behind the lackoffluorescence in solution is a2 '-hydroxychalcone derivative( HC1, Figure 2). [46,76] The PES for this molecule has been studied recently together with the effect of electrostatic interactions on the non-radiative rate in the solid phase. The resultsa re presented in Section4.2 in the contexto fi ntermolecular effects.…”
Section: Esipt Compounds-hydroxyphenylimidazopyridine (Hpip) and 2'-hmentioning
confidence: 99%
“…In contrast, in condensed phases, a molecule's freedom of nuclear reorganization is hindered by the close packing imposed by its environment. The study of the effect of this close packing on excited‐state PESs and photochemical behavior is a vast topic and involves an accumulation of inter‐related factors both electronic and nuclear in nature which are often hidden behind the deceptively concise term of steric hindrance …”
Section: Featuresmentioning
confidence: 99%
“…Both HC and DMAP can experience excited‐state intramolecular proton transfer, splitting the excited state into two potential decay pathways. It was recently computationally shown that in HC, both the enol and the keto nonradiative decay pathways were rendered energetically inaccessible by a combination of molecular and crystalline factors …”
Section: Featuresmentioning
confidence: 99%
“…The general ESIPT process starts from the ground-state enol form and ends by returning to the same state after the so-called four-level reaction cycle. [27][28][29][30][31][32][33][34][35][36][37][38] Most recent cutting-edge application seems to be focused on lighting materials. The difference between the two Stokes shifts could be as large as 6,000-12,000 cm −1 .…”
Section: Introductionmentioning
confidence: 99%